Service Quality and Customer Satisfaction as Determinants of Customer Loyalty (Study of Warung Bude88 Binjai Market) - Irwan Dwi Julianto; Yasir Hudzaifah; Wulan Purnama Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The culinary industry is part of the rapidly growing Micro, Small and Medium Enterprises (MSMEs) and has a lot of competition. Warung Bude88 is one of the businesses trying to stay competitive. This study analyzes the effect of service quality and customer satisfaction on customer loyalty at Warung Bude88. The research was conducted using quantitative methods through questionnaires, interviews, and observations with 100 customers as samples. Data analysis includes validity, reliability, normality, linearity, multicollinearity, multiple linear regression, correlation coefficient (R), coefficient of determination (R²), simultaneous test (F), and partial test (t). The results showed that service quality and customer satisfaction have a major impact on customer loyalty, with an influence of 38.6%. Meanwhile, 61.4% of customer loyalty is influenced by other factors not discussed in this study.